Anthropometric Evaluation of Foramen Ovale in Adult Dry Skulls of the Mysuru-based Population - Srikantaiah, Vidya C.; Shetty, Hemamalini (Journal of Morphological Sciences, 2019)
Introduction The greater wing of sphenoid presents various foramina, of which the foramen ovale is one important foramen through which advanced surgical therapeutic and diagnostic procedures related to the middle cranial fossa are performed.Materials and Methods A total of 40 dried adult skulls of unknown gender and age, obtained from the Department of Anatomy of the JSS medical College, Mysuru, Kamakata, India. The length and the width of the foramen ovale were measured using digital sliding calipers (tiny deal 150 mm SS digital caliper with LCD display, Kristeel-Shimwa industries, Bombay, India).Results The mean length of the foramen ovale was 0.745 ± 0.31 cm on the right side (RS), and 0.68 ± 0.15 cm on the left side (LS). The mean width was 0.6 ± 0.17 cm on the RS, and 0.56 ± 0.14 cm on the LS.Conclusion The knowledge of variations in the length and breadth of the foramen ovale is of immense importance in neurosurgery during various invasive surgical procedures, such as percutaneous trigeminal rhizotomy, and in the biopsy of cavernous sinus tumors and of Meckel cave lesions.
Keywords: foramen ovale; greater wing of sphenoid; middle cranial fossa; mandibular nerve